Upaya Meningkatkan Motivasi Belajar Siswa Dalam Pembelajaran PJOK Melalui Permainan Tradisional Engklek - Nanang Kurniawan; Anung Priambodo; Marsudianto Marsudianto (BADAN PENERBIT STIEPARI PRESS, 2024)
Physical Education is a systematic process that aims to improve students' physical and mental health through physical activity. Despite having clear goals, the reality is that many students are less motivated in learning movement skills, preferring games or matches. This research aims to increase the learning motivation of students in grade 4 in learning Physical Education, Health, and Recreation (PJOK) through the application of the traditional game of engklek. Traditional games are expected to create a fun and interesting learning atmosphere, as well as expand students' movement experience. The observation results showed that the lack of game variety caused students' lazy attitude. With the implementation of engklek, it is hoped that students' learning motivation will increase, so that they are more active and involved in PJOK learning. This research is entitled